PERAN FASILITATOR KARANG TARUNA DALAM MENGEMBANGKAN DESTINASI AIR TERJUN LABURAN DI DESA SINGKI KEC ANGGERAJA KAB ENREKANG - Fatwa, Muhammad; aeminb, muh (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2024)
This research aims to (1) Describe and analyze the role of facilitators in developing tourist destinations, (2) Reveal data regarding how Waterfall tourist destinations are implemented in community empowerment, (3) Analyze facilitators' obstacles in developing tourist destinations. Data collection was carried out by interviews, observation and documentation. The techniques used in data analysis are data reduction, data presentation, and drawing conclusions. Triangulation is used to explain the validity of the data by using source triangulation. Based on the results of the research, it is hoped that it will bring about changes in the important role of all aspects of supporting the ideas of youth youth organizations in Singki Village in building a Laburan waterfall tourist attraction. It is hoped that it will be able to introduce the potential of the village.Keywords: Role of Facilitator, Karang Taruna, Waterfall Destination.